A New HP–UHP Eclogite Belt Identified in the Southeastern Tibetan Plateau: Tracing the Extension of the Main Palaeo-Tethys Suture Zone. (11th July 2020) - Wang, Huining; Liu, Fulai; Sun, Zaibo; Ji, Lei; Zhu, Jianjiang; Cai, Jia; Zhou, Kun; Li, Jing
Abstract: The Changning–Menglian orogenic belt (CMOB) in the southeastern Tibetan Plateau is an important link between the Longmu Co–Shuanghu suture (LCSS) in the northern Tibetan Plateau and the Chiang Mai–Inthanon and Bentong–Raub sutures in Thailand and Peninsular Malaysia. These belts and sutures are generally regarded as containing the remnants of the oceanic crust of the Palaeo-Tethys that formed by seafloor spreading as a result of the separation of Gondwana- and Eurasia-derived blocks during the Middle Cambrian. In this paper we report the first discovery of abundant unaltered and retrograde eclogites that occur as irregular lenses and blocks in metasedimentary rocks of the CMOB, and these eclogites form an elongate and almost north–south-trending high-pressure (HP)–ultrahigh-pressure (UHP) metamorphic belt that is ∼200 km long and ∼50 km wide. The newly discovered phengite/talc/epidote–glaucophane eclogites, lawsonite–talc–phengite eclogites, dolomite/magnesite–kyanite eclogites and phengite–kyanite-bearing retrograde eclogites have enriched (E-) and normal mid-ocean ridge basalt (N-MORB)-like affinities and mainly positive as well as some negative whole-rock εNd values (–4·34 to +7·89), which suggest an enriched and depleted oceanic lithosphere source for their protoliths. Magmatic zircons separated from the epidote–glaucophane, magnesite–kyanite and (phengite–kyanite-bearing) retrograde eclogites gave protolith ages of 317–250 Ma, which fit well within the time frame of the opening of the Palaeo-Tethys during the Middle Cambrian and its closure during the Triassic. Abundant metamorphic zircons in the eclogites indicate a Triassic metamorphic event related to the subduction of the Palaeo-Tethys oceanic crust from 235 to 227 Ma. Taking into account previous isotopic age data, we now establish the periods of Early–Middle Triassic (246–227 Ma) and Late Triassic (222–209 Ma) as the ages of subduction and exhumation of the Palaeo-Tethyan oceanic crust, respectively. Thermodynamic modelling revealed that the eclogites record distinct HP–UHP peak metamorphic conditions of 23·0–25·5 kbar and 582–610 °C for the phengite–glaucophane eclogites, 24·0–25·5 kbar and 570–586 °C for the talc–glaucophane eclogites, 29·0–31·0 kbar and 675–712 °C for the dolomite–kyanite eclogites, and 30·0–32·0 kbar and 717–754 °C for the magnesite–kyanite eclogites. These P – T estimates and geochronological data indicate that the Palaeo-Tethys oceanic slab was subducted to different mantle depths from 75 km down to 95 km, forming distinct types of eclogite with a variety of peak eclogite-facies mineral assemblages. The eclogites consistently record clockwise metamorphic P – T – t paths characterized by a heating–compression prograde loop under a low geothermal gradient of 5–10 °C km –1, indicating the rapid subduction of cold oceanic crust at a rate of 4·5–6·0 km Ma –1, followed by isothermal or cooling–decompressive retrogression and exhumation at an average rate of 3·2–4·2 km Ma –1 . The newly discovered eclogites of the CMOB with their signatures of ocean-crust subduction are petrologically, geochemically and geochronologically comparable with those of the LCSS, providing powerful support for the idea that a nearly 2000 km long HP–UHP eclogite belt extends from the northern Tibetan Plateau to the southeastern Tibetan Plateau, and that it represents the main boundary suture of the Palaeo-Tethyan domain. These results have far-reaching implications for the tectonic framework and complex metamorphic evolution of the Palaeo-Tethyan domain.